Digital technologies in territorial development: Opportunities and challenges of application in state and municipal administration - Ivan A. Antipin; Natalya Yu. Vlasova; Elena A. Shishkina (Управленец)
Digital technologies are introduced into state and municipal administration with a view of strengthening interaction of authorities of different levels with each other and the population, as well as increasing the speed and quality of decision-making. At the same time, digital transformation processes at regional and municipal levels are highly differentiated. The paper delves into theoretical, methodological and practical aspects of the use of digital technologies in territorial development and looks at oppor tunities for their application in state and municipal administration. Methodologically, the study rests on the theories of regional growth and strategic management, spatial theory, and the concept of digital society. Synthesis, data analysis, visualization, and ex pert assessment are applied as research methods. Empirical data are retrieved from the Federal State Statistics Service (Rosstat) and regulatory documents on the development of the RF subjects. Our study confirms that digitalization is becoming a critical factor in long-term territorial development. We have systematized the types of digital technologies employed in governance processes and revealed that their use by state authorities and local self-governments (SAs and LSGs) is highly differentiated. The Ural and Central Federal Districts are leaders in the use of digital technologies. The findings indicate the need for cultivating mutual consistency and integration of digital transformation strategies and regional development strategies. To ensure effective digitalization of territories at different levels, it is necessary to define the boundaries and standards for the use of digital technologies, develop technical com petencies of decision-makers, guarantee information security and protection of personal data, and reduce fraud risk.